2021
DOI: 10.1016/j.dsx.2021.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to telemedicine in the COVID-19 era: Feasibility of dried blood spot testing for hemoglobin A1c

Abstract: Background and aims The COVID-19 pandemic has led to a rapid growth in the use of telemedicine for delivery of ambulatory diabetes care. This study evaluated the feasibility of remote HbA1c monitoring via dried blood spot (DBS) testing to support assessment of glycemic control for telemedicine visits and examined clinical and demographic characteristics associated with patient completion of DBS testing. Methods Providers could place orders for DBS HbA1c 3 weeks prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Good concordance has been reported in the literature for HbA 1c measured in capillary and venous blood samples using both dried blood spot devices and collection tubes 9,16–19 . Two previous studies reported that 69.2% and 70% of participants, respectively, would use a remote HbA 1c service if available or recommend this service 1,16 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Good concordance has been reported in the literature for HbA 1c measured in capillary and venous blood samples using both dried blood spot devices and collection tubes 9,16–19 . Two previous studies reported that 69.2% and 70% of participants, respectively, would use a remote HbA 1c service if available or recommend this service 1,16 .…”
Section: Discussionmentioning
confidence: 76%
“…Good concordance has been reported in the literature for HbA 1c measured in capillary and venous blood samples using both dried blood spot devices and collection tubes. 9 , 16 , 17 , 18 , 19 Two previous studies reported that 69.2% and 70% of participants, respectively, would use a remote HbA 1c service if available or recommend this service. 1 , 16 Our study gave similar results with over three quarters of respondents (75.4% [43/57]) reporting that they would use the remote HbA 1c service routinely if available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even during the most restricted lockdown, an Italian group of patients using rt-CGM and followed by telemedicine did not show worsening of their glycemic controls [71]. In another group tested during pandemics, results demonstrated that remote HbA1c monitoring via dried blood spot is feasible and offers an avenue to support assessment of glycemic control for patients seen via telemedicine [72]. Assessments from survey on people with type 1 diabetes during lockdown showed that at least two-thirds underwent changes in the management of their condition [73].…”
Section: Telemedicine-routine Daily Carementioning
confidence: 98%
“…To collect a sample the patient performs a finger prick and places one or two drops of capillary blood onto a DBS card, which is then sent to a laboratory for elution and analysis. In the setting of the COVID-19 pandemic, the DBS method has been shown to be a useful remote monitoring tool for the delivery of routine ambulatory care while minimizing hospital visits and the risk of virus exposure [ 7 , 8 ]. A remote monitoring method such as DBS sampling would be beneficial to monitor IgG levels in patients with PID who are at high risk of infections.…”
Section: Introductionmentioning
confidence: 99%